1973
DOI: 10.2307/3664987
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art of Working Capital Management

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Financial Management Association International are collaborating with JSTOR to digitize, preserve and extend access to Financial Management. He is the author of Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
3

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 13 publications
1
46
0
3
Order By: Relevance
“…The lack of understanding about its impact on profitability, the lack of clarity about its key factors, the lack of management ability to plan and control working capital components may lead to insolvency and bankruptcy. Smith (1973) suggested that many businesses have failed due to the inability of financial managers to plan and control current assets and current liabilities in their companies. In Brazil, a recent study with 14,181 small companies had the same findings (SEBrAE, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The lack of understanding about its impact on profitability, the lack of clarity about its key factors, the lack of management ability to plan and control working capital components may lead to insolvency and bankruptcy. Smith (1973) suggested that many businesses have failed due to the inability of financial managers to plan and control current assets and current liabilities in their companies. In Brazil, a recent study with 14,181 small companies had the same findings (SEBrAE, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The availability of cash dictates whether the firm can pay employees, suppliers, banks, landlords, and even the owner's salary; in short, small business management is cash flow management. However, it is widely recognized that small firms face serious difficulties when it comes to managing cash and working capital (Dodge, Fullerton, and Robbins, 1994), and that ineffective management of working capital is prevalent in small firms (Dunn and Cheatham, 1993;Berryman, 1983;Smith, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…According to Eljelly (2004), the management of working capital is both the planning and the handling of current assets and current liabilities to reduce the default risk or the chance in which companies or individuals will be unable to make the required payments on their debt obligations at a certain period of time, while on the other side it is essential to avoid investment on excessive assets. When a company experience operational difficulties or, in other words, cannot maintain its business properly, it may lead to bankruptcy (Smith, 1973). In the United States, a department store filed for bankruptcy after experiencing cash flow deficit in its operational activity for eight years in the past 10 years (Largay and Stickney, 1980).…”
Section: Introductionmentioning
confidence: 99%